2011
DOI: 10.1007/s11605-010-1248-1
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Orthotopic Liver Transplantation for Hemorrhage from a Giant Cavernous Hepatic Hemangioma: Case Report and Review

Abstract: IntroductionCavernous hemangiomas represent the most common benign primary hepatic neoplasm, often being incidentally detected. Although the majority of hepatic hemangiomas remain asymptomatic, symptomatic hepatic hemangiomas can present with abdominal pain, hemorrhage, biliary compression, or a consumptive coagulopathy. The optimal surgical management of symptomatic hepatic hemangiomas remains controversial, with resection, enucleation, and both deceased donor and living donor liver transplantation having bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 22 publications
0
48
0
Order By: Relevance
“…However, in some patients the location and size of the lesion can cause various signs and findings. According to a previous study, 4 although 40% of hemangioma about 4 cm in diameter are symptomatic, 90% of those approximately 10 cm in diameter are symptomatic. The most frequently seen symptom is pain in the right upper quadrant.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, in some patients the location and size of the lesion can cause various signs and findings. According to a previous study, 4 although 40% of hemangioma about 4 cm in diameter are symptomatic, 90% of those approximately 10 cm in diameter are symptomatic. The most frequently seen symptom is pain in the right upper quadrant.…”
Section: Discussionmentioning
confidence: 91%
“…[1][2][3]6 Hemangioma are often seen between the ages of 30 and 50 years and 5 to 6 times more often in women than in men. 4,6,7,9,10 Therefore, it has been suggested that there may be a relationship between the disease and the use of exogenous steroids or female-specific hormones, although the relationship has not been clearly shown. 2,3,10 Because most hepatic hemangioma are asymptomatic, they are often recognized incidentally during radiologic tests for other reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery includes liver resection, enucleation and transplantation [29]. A rare cases of liver transplantation performed for diffuse hepatic hemangiomatosis, lesions anatomically unresectable by conventional approaches and in patients with Kasabach-Merritt syndrome, have been reported [7][8][9][10]. However there is a shortage of liver graft and the need of a long-term anti-immunologic treatment in transplanted patients.…”
Section: Surgical Approachmentioning
confidence: 99%
“…A hemangioma can be removed by enucleation or liver resection however, most authors advocated enucleation procedure. In very rare and exceptional condition, Liver transplantation can be considered as a treatment option for hemangioma [7][8][9][10]. Other therapeutic options as Radiofrequency ablation (RFA) and transcatheter arterial embolization (TAE) can be considered in some situations.…”
Section: Introductionmentioning
confidence: 99%